Pelatihan Usaha Pengelasan Bagi Siswa Pondok Pesantren AS SAADAH Puri Serpong - Bambang Herlambang; Budi Kaliwanto; Deden Rosid Waltam (Pusat Riset dan Inovasi Nasional, 2023)
The welding business can be one of the business opportunities that can be developed in a business because the profits from the welding business are also very promising. The partners in this PKM activity are the students of the As Saadah Puri Serpong Islamic Boarding School as an alternative business opportunity to run a welding business. The welding business needs to be carried out with adequate knowledge and planning. This is so that the welding business can develop properly and experience an increase in terms of turnover and profit. Based on the results of observations and discussions with the two partners, there were several problems encountered both in the process of selecting locations, equipment, business design, execution processes and marketing. There is no adequate knowledge of welding technology and important things that must be considered in running a welding business, so it is considered necessary to provide training so that the welding business can be carried out with good planning and supervision. The solutions proposed or offered in this PKM activity are as follows: 1. Aspects of production: In accordance with the problems faced by the two partners, solutions for business aspects include: a. creating a guiding model regarding quality management both in the process of selecting tools and materials as well as in the welding process. B. By applying painting technology with paint that dries faster than ordinary paint. 2. Management aspect: The solution offered to partners is to provide business/business management training covering planning to control both in production and management aspects. 3. Aspects of customer convenience and satisfaction: The solution offered to partners is to provide a strategy for making customers comfortable and satisfied when performing welding services, so that customers do not only make fences and trellis once, but will come back and come back again because they feel comfortable and satisfied with service. They will become loyal customers, even customers who will attract other potential customers.